The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/aos.12082
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure reduction with topical medications and progression of normal‐tension glaucoma: a 12‐year mean follow‐up study

Abstract: ABSTRACT.Purpose: To investigate whether the amount of intraocular pressure (IOP) reduction with topical medications is associated with the progression of normal-tension glaucoma (NTG) and to identify risk factors for NTG progression. Methods: The medical records of 121 eyes of 121 NTG patients, who were treated with topical medications for more than 7 years, were reviewed. NTG progression was defined by either structural (optic disc or retinal nerve fibre layer) or functional (visual field) deterioration. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 36 publications
(72 reference statements)
2
32
1
Order By: Relevance
“…The hallmark feature of glaucoma is damage and loss of retinal ganglion cells (RGCs), the neurons that connect the eyes to the brain (Quigley, 1999;Weinreb and Khaw, 2004;Casson et al, 2012). Glaucoma is often associated with elevated intraocular pressure (IOP;Sommer, 1989;Peters et al, 2014) and pressure-lowering agents can be effective in slowing RGC loss (Morrison et al, 1998;Heijl et al, 2002;Kass et al, 2002;Lichter, 2002;Kim et al, 2013). Even with pressurelowering drugs, however, RGCs eventually die.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmark feature of glaucoma is damage and loss of retinal ganglion cells (RGCs), the neurons that connect the eyes to the brain (Quigley, 1999;Weinreb and Khaw, 2004;Casson et al, 2012). Glaucoma is often associated with elevated intraocular pressure (IOP;Sommer, 1989;Peters et al, 2014) and pressure-lowering agents can be effective in slowing RGC loss (Morrison et al, 1998;Heijl et al, 2002;Kass et al, 2002;Lichter, 2002;Kim et al, 2013). Even with pressurelowering drugs, however, RGCs eventually die.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to IOP-related parameters in NTG patients, insufficient IOP reduction 36,38,113 and large IOP fluctuation 39 were found to be significant risk factors for progression. Therefore, major therapeutic goals for NTG patients include achievement of a large extent of IOP reduction and maintenance of low and stable IOP.…”
Section: Monitoring Of Structural and Functional Progressionmentioning
confidence: 99%
“…33 Such findings were also seen in NTG patients similar to POAG patients, indicating that hyperbaric damage also plays a role even in eyes within the IOP reference range. 34 Based on the multitude of epidemiologic studies (conducted in populations with large NTG proportions) reporting high IOP as a common risk factor 15,16,22,35 and longitudinal studies reporting clinical treatment outcomes in NTG patients, [36][37][38][39] it can be concluded that there is a protective effect of IOP-lowering treatment for NTG patients. Moreover, despite NTG patients having IOP within the reference range, epidemiological data have confirmed significantly higher IOPs than those of control subjects.…”
Section: Iop-dependent Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low IOP after treatment, approximately 50% of patients with NTG had VF damage progression as detected by perimetry (120,121) . It is possible that patients with this condition have a lower threshold for IOP mechanical injury than those with other glaucoma phenotypes and that more substantial IOP reduction is often necessary compared with the one achieved with topical medications or trabeculoplasty.…”
Section: Laser and Surgical Treatmentmentioning
confidence: 99%